Stay or go: the effects of migration and return decisions on human capital formation - Sadıkoğlu, Serhan. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
In this thesis, I study the migration and return migration decisions of skilled workers, along with the the impact of migration prospects on human capital formation under asymmetric information. Moreover, I analyze the dynamics of migration and return migration as information asymmetries and migration costs evolve over time. I find that skilled migration is followed by return migration which involves both positive and negative selection of skilled migrants. Furthermore, I show that the possibility of migration has a positive impact on human capial formation in the source country and derive the conditions required for a possibility of a welfare gain in the source country to be observed.
Keywords: Human capital.; Emigration and immigration -- Economic aspects.